Frontiere del corpo, frontiere del diritto: intersessualità e tutela della persona (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
The paper examines the medical practices imposing cosmetic surgeries on intersex children, which aims at conforming their genitalia to a perfect male or female body. Furthermore, it focuses on the legal approaches that could be adopted to challenge these medical practices and to ensure the protection of children’s rights.
Keywords: Intersex; Health; Protection; Bodily Integrity; Fundamental Rights